Mathematical Analysis of Side effects of HIV/AIDS Medication (Bangladesh Journal of Medical Science, 2014)
Acquired Immune deficiency syndrome (AIDS) is caused by Human immunodeficiency virus (HIV); More than 40 Million people live with HIV worldwide. Various antiretroviral classes of drugs are used to treat HIV infection and the prolonged treatment has to be taken for the rest of life. It is very difficult to continue prolonged treatment because of problem of adherence and side effects. The basic purpose of antiretroviral treatment is to maintain the quality of life of a patient. However, these side effects vary from drug to drug and patient to patient. The objective of this research is to be modeled some major drug induced side effects by using fuzzy matrix theory which is one of the best tools to analyze unsupervised data involving imprecision. This study is of interest for HIV Specialist and physician who care for HIV/AIDS patients with an aim to concentrate more on safety profile of HIV/AIDS drugs. DOI: http://dx.doi.org/10.3329/bjms.v13i2.13884 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.119-123